2018
DOI: 10.7189/jogh.08.021101
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional estimates of the morbidity due to type I diabetes among children aged 0-4 years: a systematic review and analysis

Abstract: BackgroundEpidemiology of type 1 diabetes mellitus (T1DM) among children aged 0-4 years globally is not well understood. We aim to assess the incidence of T1DM in low- and middle-income countries (LMIC) by conducting a systematic review of previous reports. We also aim to address possible contribution to child mortality and to identify any temporal trends.MethodsA systematic review was performed using a carefully designed search strategy to explore MEDLINE, EMBASE and Global Health databases. Data was extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 98 publications
0
4
1
Order By: Relevance
“…A recent systematic review reported that the overall pooled incidence of T1D in children aged 0-4 years globally is 11.2 per 100,000 child-years, accounting for 100,000-150,000 cases among new diagnosis of T1D each year in the world. Highest rates were identified in European countries [6]. In our experience, the crude incidence rate in younger children was higher compared to these data.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…A recent systematic review reported that the overall pooled incidence of T1D in children aged 0-4 years globally is 11.2 per 100,000 child-years, accounting for 100,000-150,000 cases among new diagnosis of T1D each year in the world. Highest rates were identified in European countries [6]. In our experience, the crude incidence rate in younger children was higher compared to these data.…”
Section: Discussioncontrasting
confidence: 49%
“…Diabetes-related chronic complications are not uncommon among adolescents and are related to severe impairment of patients' quality of life [5]. Furthermore, mortality from T1D has been reported also in the pediatric population, especially in Africa and many low-and middle-income countries [6]. Although in recent years several clinical trials aimed at preventing T1D onset have been conducted [7,8], established and approved strategies are still lacking and T1D remains a widespread public health concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion deserves our attention. According to Adeloye D [ 16 ], the incidence of T1DM in children aged 0–4 years is rising worldwide, and was 20.9 (7.8–34.1) per 100,000 child years in 2015. The incidence of T1DM is shifting towards younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…T1D is observed more commonly in European people, with Finland reporting >60 cases per 100,000 people each year following Sardinia, around 40 cases per 100,000 people each year [ 19 ]. Across the globe, the incidence of T1D is increasing by 3% every year, although profound reasons for this are unclear [ 20 , 21 , 22 , 23 ].…”
Section: Epidemiology Of T1dmentioning
confidence: 99%